Synthesis and chemical and structural characterization of hydroxyapatite obtained from eggshell and tricalcium phosphate (2016)
(Eng) The eggshell is a common residue that is usually discarded without giving any use to it. In this paper the results obtained from a proposed procedure to get hydroxyapatite (HA) from eggshell are shown. The HA is a calcium phosphate which has been widely used as implant material due to the close similarity of its composition with the inorganic phase of natural bone. HA generally has a high cost and it is presented as micro and nanostructured bioceramics; the last one is a promising option for tissue engineering nanotechnology. In this study, results of X-ray diffraction (XRD) showed the hydroxyapatite production exhibiting the characteristic peaks of this material for the cubic phase fcc (111), (102), (211), and for the hexagonal phase hcp (h-211) and (h-322). From the results of Fourier transform infrared spectroscopy (FTIR), it was possible to determine the active modes of vibration corresponding to hydroxyapatite (Ca10 (PO4)6(OH)2). From the results of scanning electron microscopy, it was determined the topography of the ceramic powder as well as its morphological distribution.